Pulse high-volume haemofiltration for treatment of severe sepsis: effects on hemodynamics and survival - Ratanarat, Ranistha (BioMed Central, 2005)
INTRODUCTION: Severe sepsis is the leading cause of mortality in critically ill patients. Abnormal concentrations of inflammatory mediators appear to be involved in the pathogenesis of sepsis. Based on the humoral theory of sepsis, a potential therapeutic approach involves high-volume haemofiltration (HVHF), which has exhibited beneficial effects in severe sepsis, improving haemodynamics and unselectively removing proinflammatory and anti-inflammatory mediators. However, concerns have been expressed about the feasibility and costs of continuous HVHF. Here we evaluate a new modality, namely pulse HVHF (PHVHF; 24-hour schedule: HVHF 85 ml/kg per hour for 6–8 hours followed by continuous venovenous haemofiltration 35 ml/kg per hour for 16–18 hours). METHOD: Fifteen critically ill patients (seven male; mean Acute Physiology and Chronic Health Evaluation [APACHE] II score 31.2, mean Simplified Acute Physiology Score [SAPS] II 62, and mean Sequential Organ Failure Assessment 14.2) with severe sepsis underwent daily PHVHF. We measured changes in haemodynamic variables and evaluated the dose of noradrenaline required to maintain mean arterial pressure above 70 mmHg during and after pulse therapy at 6 and 12 hours. PHVHF was performed with 250 ml/min blood flow rate. The bicarbonate-based replacement fluid was used at a 1:1 ratio in simultaneous pre-dilution and post-dilution. RESULTS: No treatment was prematurely discontinued. Haemodynamics were improved by PHVHF, allowing a significant reduction in noradrenaline dose during and at the end of the PHVHF session; this reduction was maintained at 6 and 12 hours after pulse treatment (P = 0.001). There was also an improvement in systolic blood pressure (P = 0.04). There were no changes in temperature, cardiac index, oxygenation, arterial pH or urine output during the period of observation. The mean daily Kt/V was 1.92. Predicted mortality rates were 72% (based on APACHE II score) and 68% (based on SAPS II score), and the observed 28-day mortality was 47%. CONCLUSION: PHVHF is a feasible modality and improves haemodynamics both during and after therapy. It may be a beneficial adjuvant treatment for severe sepsis/septic shock in terms of patient survival, and it represents a compromise between continuous renal replacement therapy and HVHF.